IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN PJOK PADA SISWA KELAS V SD NEGERI 15 BANDA ACEH - Shibgha Tullah; Ully Muzakir; Mahmudin Aritanoga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is an essential pillar in addressing the challenges of moral decline in the Society 5.0 era. This study aims to measure and describe the implementation of character education through Physical Education, Sports, and Health lessons among fifth-grade students at SD Negeri 15 Banda Aceh. This study employs a quantitative descriptive approach using a survey method involving 30 students as the total population (total sampling). Data collection was conducted via a closed-ended questionnaire consisting of 32 items, which had been validated for validity and reliability (Cronbach’s Alpha 0.913), and was reinforced through source triangulation using evaluations by the PJOK teacher. Analysis results indicate that the overall level of character implementation among students falls into the Very Good category, with a percentage of 73%. Specifically, the religious factor achieved the highest score, with all students in the Very Good category, followed by the discipline and orderliness factor at 93%. However, the healthy lifestyle factor and the creative dimension still show a distribution in the Fair category (17%), requiring more intensive guidance. The study concluded that physical activity in Physical Education is effective as a behavioral laboratory for the development of student character, although it requires synergy between schools and facilities to optimize the adoption of a healthy lifestyle.